The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s002237782200006x
|View full text |Cite|
|
Sign up to set email alerts
|

Turbulence mitigation in maximum-J stellarators with electron-density gradient

Abstract: In fusion devices, the geometry of the confining magnetic field has a significant impact on the instabilities that drive turbulent heat loss. This is especially true of stellarators, where the density-gradient-driven branch of the ‘trapped electron mode’ (TEM) is predicted to be linearly stable if the magnetic field has the maximum-J property, as is very approximately the case in certain magnetic configurations of the Wendelstein 7-X experiment (W7-X). Here we show, using both analytical theory and simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
(62 reference statements)
2
23
0
Order By: Relevance
“…(2012) and Proll et al. (2022), which consider a plasma instability which moves a particle radially by . The energy required to do so, , can be found through the conservation of both and the cumulative energy of the particle and instability () Because (see (1.3)), we see that will be negative when .…”
Section: Introductionmentioning
confidence: 80%
“…(2012) and Proll et al. (2022), which consider a plasma instability which moves a particle radially by . The energy required to do so, , can be found through the conservation of both and the cumulative energy of the particle and instability () Because (see (1.3)), we see that will be negative when .…”
Section: Introductionmentioning
confidence: 80%
“…As usual, the temperature gradient scale length is measured relative to the minor radius, a/L T = −(a/T )dT /dr. To study the most unstable ITG mode conditions, we neglect certain stabilizing factors such as the density gradient [22,23] and plasma beta (electromagnetic effects) [24].…”
mentioning
confidence: 99%
“…This, however, grants none of the properties beneficial to TEM stability possessed by locally maximum-J configurations. Interestingly, it has been found that HSX performs well in nonlinear simulations of turbulent transport, despite the less favourable stability properties (McKinney et al 2019;Proll et al 2022).…”
Section: Stellarator Configurations Consideredmentioning
confidence: 99%
“…To investigate how the linear universal modes identified at in the high-mirror configuration of W7-X in § 4 translate to nonlinear simulations, we examine the nonlinear W7-X high-mirror simulations recently published by Proll et al. (2022). These simulations were carried out at a density gradient of , which facilitates comparison with the linear results in § 4 while also being in the experimentally relevant density-gradient range.…”
Section: Evidence Of Universal Modes In Nonlinear Simulations In W7-xmentioning
confidence: 99%